2017
DOI: 10.1002/adma.201700527
|View full text |Cite
|
Sign up to set email alerts
|

Iodine Vacancy Redistribution in Organic–Inorganic Halide Perovskite Films and Resistive Switching Effects

Abstract: Organic-inorganic halide perovskite (OHP) materials, for example, CH NH PbI (MAPbI ), have attracted significant interest for applications such as solar cells, photodectors, light-emitting diodes, and lasers. Previous studies have shown that charged defects can migrate in perovskites under an electric field and/or light illumination, potentially preventing these devices from practical applications. Understanding and control of the defect generation and movement will not only lead to more stable devices but als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
281
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 304 publications
(293 citation statements)
references
References 41 publications
12
281
0
Order By: Relevance
“…[42,43] Several recent studies have also started to explore controlled ion migrations in materials such as organic-inorganic halides (e.g., CH 3 NH 3 PbI 3 ), [44] which have attracted broad interest as a promising optoelectronic material for solar cell, [45] photodetector, [46] light-emitting diodes, [47] and laser [48] applications. [49] Moreover, more iodine vacancies were observed near the cathode, indicating the growth of iodine vacancy filaments was initiated from the cathode and extended to the anode. For example, in the Ag/CH 3 NH 3 PbI 3 /Ag RS system (Figure 2f), it was shown that the I:Pb atomic ratio in the CH 3 NH 3 PbI 3 film can be significantly decreased at LRS, then partially restored at HRS.…”
Section: Anion-driven Rs Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…[42,43] Several recent studies have also started to explore controlled ion migrations in materials such as organic-inorganic halides (e.g., CH 3 NH 3 PbI 3 ), [44] which have attracted broad interest as a promising optoelectronic material for solar cell, [45] photodetector, [46] light-emitting diodes, [47] and laser [48] applications. [49] Moreover, more iodine vacancies were observed near the cathode, indicating the growth of iodine vacancy filaments was initiated from the cathode and extended to the anode. For example, in the Ag/CH 3 NH 3 PbI 3 /Ag RS system (Figure 2f), it was shown that the I:Pb atomic ratio in the CH 3 NH 3 PbI 3 film can be significantly decreased at LRS, then partially restored at HRS.…”
Section: Anion-driven Rs Effectsmentioning
confidence: 99%
“…Sulfur vacancy-induced doping effect has also been used by Sangwan et al to explain the RS effect in devices based on chemical-vapor-deposition-(CVD)grown monolayer MoS 2 film. [49] Copyright 2017, John Wiley & Sons, Inc. i) Schematic illustration of a few-layer MoS 2 device with Ti/Au electrodes. [32] Copyright 2010, Springer Nature.…”
Section: Anion-driven Rs Effectsmentioning
confidence: 99%
“…Recently, Guan et al suggested that migration of MA vacancies in the layer and modulation of the Schottky barrier at the perovskite/ITO interface may also contribute to resistive switching in OIPbased memory. [49] Copyright 2017, John Wiley & Sons. The MAPbBr 3 and ITO bottom electrode formed a Schottky junction.…”
Section: Wwwadvelectronicmatdementioning
confidence: 99%
“…[42][43][44][45] However, OIP-based photovoltaic device exhibits difference in current-voltage curve (hysteresis) under forward and reverse scanning directions which is undesirable in optoelectronic applications. [47][48][49][50][51][52][53][54][55][56][57][58][59][60][61] Moreover, OIPs are photosensitive, and this trait can be exploited in device with photon recording functionality. [47][48][49][50][51][52][53][54][55][56][57][58][59][60][61] Moreover, OIPs are photosensitive, and this trait can be exploited in device with photon recording functionality.…”
mentioning
confidence: 99%
“…Unlike these materials, OHPs benefit considerably from their mixed ionic‐electronic conduction behavior, that is, the halide counterions of OHPs are mobile under an electric field . In particular, novel unique functions can be developed with OHP‐based memristors that take advantage of the remarkable photoabsorption ability of this emerging material system through synergistic coupling of photonic, electronic, and ionic processes …”
Section: Introductionmentioning
confidence: 99%